The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1111/j.1365-2133.2005.07041.x
|View full text |Cite
|
Sign up to set email alerts
|

Mutation analysis in Irish families with glomuvenous malformations

Abstract: Summary Background  Glomuvenous malformations (GVMs) are rare bluish lesions that can affect the skin and mucosal surfaces. They represent defects in vasculogenesis. Lesions can occur sporadically or in an autosomal dominant mode of inheritance. Recent studies have shown that mutations in the glomulin gene (GLMN) on chromosome 1p21‐22 are responsible for familial GVMs. Objectives  To search for mutations in GLMN in Irish families with GVMs. Methods  We identified four Irish families with GVMs and confirmed lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…If lesions are extensive, surgical resections become impractical. Sclerotherapy with sodium chloride and sodium tetradecolecylsulfate, electron bean radiation, argon, and carbon dioxide lasers have been attempted with variable success rates in treating extensive GVM (29–35). Treatment of large, extensive and disfiguring lesions remains difficult.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If lesions are extensive, surgical resections become impractical. Sclerotherapy with sodium chloride and sodium tetradecolecylsulfate, electron bean radiation, argon, and carbon dioxide lasers have been attempted with variable success rates in treating extensive GVM (29–35). Treatment of large, extensive and disfiguring lesions remains difficult.…”
Section: Discussionmentioning
confidence: 99%
“…To this date, there have been 17 different glomulin mutations identified in 43 GVM families tested by Brouillard et al as summarized in Table 2 (11). Interestingly, O’Hagan et al also studied four separate Irish families with GVM and found that all four families had the most common mutation‐ 157delAAGAA (29). There have been no genotype–phenotype associations, and the position of a specific glomulin mutation does not correlate with clinical findings such as location, extent and number of lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Of the more than 30 mutations identified in more than 100 families, 11 account for .80% of patients (Brouillard, et al 2002(Brouillard, et al , 2005(Brouillard, et al , 2008O'Hagan et al 2006;P Brouillard, LM Boon, JB Mullikan, et al, unpubl.). The identification of the first somatic second-hit in a vascular anomaly, a 5-bp deletion in glomulin, provided evidence for a paradominant mode of inheritance (Brouillard et al 2002).…”
Section: Glomuvenous Malformationmentioning
confidence: 99%
“…In the above mentioned article 3 there was an error in the author listing. F. Maloney should have appeared as follows:…”
mentioning
confidence: 99%